Pillararene Host–Guest Complexation Induced Chirality Amplification: A New Way to Detect Cryptochiral Compounds - Zhu, Huangtianzhi; Li, Qi; Gao, Zongchun; Wang, Hongliang; Shi, Bingbing; Wu, Yitao; Shangguan, Liqing; Hong, Xin; Wang, Feng; Huang, Feihe (Angewandte Chemie International Edition, 2020)
The contradiction between the rising demands of optical chirality sensing and the failure in chiral detection of cryptochiral compounds encourages researchers to find new methods for chirality amplification. Inspired by planar chirality and the host–guest recognition of pillararenes, we establish a new concept for amplifying CD signals of cryptochiral molecules by pillararene host–guest complexation induced chirality amplification. The planar chirality of pillararenes is induced and stabilized in the presence of the chiral guest, which makes the cryptochiral molecule detectable by CD spectroscopy. Several chiral guests are selected in these experiments and the mechanism of chiral amplification is studied with a non‐rotatable pillararene derivative and density functional theory calculations. We believe this work affords deeper understanding of chirality and provides a new perspective for chiral sensing. Intrinsic advantages and uniqueness in chirality amplification are exhibited by pillararenes. By combining high affinity for guests, detectable UV absorption, and inducible chirality they can be used for detecting cryptochiral compounds.